The development of the teaching model, which combines Task-Based Learning Management with Inquiry-Based Learning Management and Creativity-Based Learning, serves as the foundation for enhancing higher-order thinking skills in Grade 5 students - Duangprom, Phisitsak (The Journal of Development Administration Research, 2024)
This research article aims to study 1) the learning management of computational science for Grade 5 students, 2) develop and validate the quality of the learning model, and (3) examine the results of implementing the model. The research follows a quantitative approach. The sample group includes 24 Grade 5 students from medium-sized schools under the Chiang Mai Primary Educational Service Area Office 6, selected through simple random sampling. The tools used in the research are: (1) a learning management model and a guidebook, (2) a higher-order thinking competency assessment, (3) lesson plans, and (4) an experience enjoyment assessment. The data were analyzed by calculating percentage, mean, standard deviation, and conducting t-tests. The research findings indicate that: 1) The learning management approach is characterized by collaborative learning comprising steps such as analysis, planning, practice, inspection, evaluation, development, and dissemination of work, grounded in socio-environmental contexts. The teacher’s role is to facilitate, guide, reinforce, and provide reflective feedback. 2) The instructional model comprises five components: (1) principles, (2) objectives, (3) the SEEAPA 6-step learning process, including Step 1: Set the Learning Issue (S), Step 2: Engage & Inspire (E), Step 3: Explore (E), Step 4: Take Act (A), Step 5: Present (P), and Step 6: Assess & Feedback (A), (4)assessment and evaluation, and (5) key conditions for successful implementation. The model demonstrated a high level of quality. And 3) the results of the model’s implementation showed that students significantly improved in all four dimensions of advanced thinking competencies at a statistical significance Additionally, students’ flow experiences with the learning model were rated at a high level.